Procedural Modeling-Based BIM Approach for Railway Design. (9th March 2021) - Biancardo, S. A.; Intignano, M.; Viscione, N.; Guerra De Oliveira, S.; Tibaut, A.
Abstract : Building information modeling (BIM) is a powerful methodological approach for designers that has revolutionized the field of architecture and construction for some years now, minimizing errors and making the entire design, construction, and management process more efficient. The first results have been so encouraging that many countries, from Europe to the United States to Asian countries, have adopted specific regulations to promote its development and use. BIM models are based on the Industry Foundation Classes (IFC) standard, i.e., an object-based file format with a data model developed by building SMART to facilitate interoperability. Objects are characterized by properties, such as geometry, material, cost, and all related construction process information, such as scheduling or the maintenance process. The 3D modeling of these objects geometric information is parametric, in order to make the design more flexible. This research work offers an insight into the possibilities offered by different BIM-based tools for parametric modeling applied in the railway sector whereby an example of a railway section model is presented. Indeed, the focus will be on the creation of parametric objects representing railway components, as existing BIM object libraries lack them in the IFC2 × 3 standard format.